Peran Sistem Informasi dalam Modernisasi Perpajakan di Indonesia - Wirawan E.I. Radianto (Jurnal Riset Manajemen dan Bisnis, 2009)
The escalating role of tac in supporting the natianal development compels the Directorate General for Taxation to apply strategies to increase the income from tax. One of those strategies is moderniztng the tmation in order ta ea$ethe tmpqters in payW the tm. Tm rnodernization aims ot improving tm services which ends up in increa.sing the obedience of the tffipmyers.  One of the ffirts employed by the Directorate Generalfor Taxation is escalating the role of information systems in order to fulfill the taxationobedience. Some of those infonnation systems are e-registration, e-SPT, and epment. This pryer discusses the wealmesses of each of these systems based. on the data collection and data analysisfrornvarious resowces.  This paper explains the result of an empirical study into how information systems of taxation influenced the obedience of the taxpayers. The research was carried out in the province of Yogtakana, which covered Bantul, Sleman, and Yogtakarta municipalities. The respondents were those taxpayers of manufactures, trade, and seryice aree$. The research result shows that tax modernization, which included e-registration, e-SPT, and e-poyment, influerced the rate of taxpqlers' obedience. The tmpayers, who used the onlinefacilities,felt positive benefi* when they,were doing their duty in paying taxes.Kqwords: tm modemization, e-SPT, e-registration, e-payrnent, informationsystem, obediencePEIIDAHT